PRODUCTIVITY AND CONDITION OF SOLID AND PARTIAL FOREST PLANTATIONS OF ENGLISH OAK IN A FRESH MAPLE-LIME OAK FOREST IN THE SKRYPAYIVSKE TRAINING & EXPERIMENTAL FOREST ENTERPRISE - Andrushchenko, O. P.; Rumіantsev M. Н.; Lunachevskyy, L. S. (Forestry and Forest Melioration, 2019)
Introduction Creation and cultivation of forest plantations are the basic tasks of modern forestry. In a fresh ash-lime fertile oak forest type of Left-bank Forest-Steppe of Ukraine, the most common type of formation of English oak (Quercus robur L.) plantations are the partial forest plantations (plantations created using partial soil tillage). Previous studies of man-made reforestation of cut areas without uprooting showed high efficiency of partial forest plantations at the age of 12. The lower cost and less labor intensity during the creation (only 40 % of the forest-cultivated area was tilled without uprooting and skidding of stumps) may lead to advantages during man-made regeneration of a forest. Materials and Methods The sample plots included the entire range of patterns of mixing and placing of forest plantations. The vital state of the trees was determined in accordance with the methodology of V. A. Alekseev. Economic calculations were performed according to the developed flow charts. The objects of the study were solid and partial trial and production forest plantations of English oak in fresh ash-lime fertile oak forest type in Skrypayivske Training & Experimental Forest Enterprise of Kharkiv National Agrarian University. Results Mixed stands with a closed canopy and English oak predominating in composition grew in all three plots. All the stands grown by the 1st site class are. Solid trial plantations slightly prevailed in mensuration indices, including standing volume. The height growth of sample oak trees was identical in two plots. As to the diameter, the partial plantations were slightly behind the solid ones (due to the positive effect of continuous soil tillage) but at the age of 43–45 became equal to them. By the vital capacity, the trees of 1st and 2nd viability categories were dominating in the studied stands in the partial trial (62.4 %) and production (86.7%) plantations and the trees of 2nd and 3rd viability categories were in solid trials (66.4%). Part of dead standing trees was significant: 12.7 % in partial trials and 10.9 % in solid ones. Creation of partial forest plantations on cut areas without uprooting of stumps required the lowest financial costs. Conclusions The partial forest plantations were equal to solid ones by the main mensuration indices and grown by the 1st site class. The lower cost value and labor input during their creation give reason to prefer them during artificial regeneration of a forest. In the partial plantations, the structure of soil, which is typical for certain forest area, is not disturbed. Also, thermal, hydrological and air conditions remain stable. Creating partial plantations will contribute to the biodiversity conservation. Creation of partial plantations with English oak without uprooting of stumps and first cleaning in fresh oak forest type could be fully mechanized. 2 Fig., 3 Tables, 12 Refs.